Kompetensi Pemecahan Masalah Mahasiswa Pendidikan Matematika dalam Membuat Grafik Fungsi Trigonometri - Welas Listiani; Firda Alfiana Patricia (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the problem-solving ability of mathematics education students at IKIP Budi Utomo in drawing trigonometric function graphs. The type of research is a case study using test and observation instruments. Students with high, medium, and low abilities can each understand the problem to make graphs of trigonometric functions, already have a plan and use a problem-solving plan in the form of choosing the method of ordered pairs, making cartesian coordinates, and drawing graphs. However, they have not reflected on the solutions already produced.